Analysis of Physical Activity Patterns using Wearable Sensors in the Management of Heart Disease - Belinda Arbitya Dewi; Agus Mukholid; Rini Ambarwati; Hermansyah Hermansyah; Arnes Yuli Vandika (Journal of World Future Medicine, Health and Nursing, 2024)
Heart disease is one of the leading causes of death worldwide. Adequate physical activity is an important factor in the management of heart disease, but accurately monitoring physical activity can be challenging. The use of wearable sensors offers a potential solution to measure and analyze physical activity patterns more precisely. This study aims to analyze physical activity patterns using wearable sensors in the management of heart disease. As well as to find out whether physical activity using wearable sensors can overcome heart disease. This research method uses a method with a quantitative approach. This study involves participants who suffer from heart disease and use wearable sensors to record their physical activity over a period of time. The physical activity data, including the number of steps, activity intensity, and activity duration, were analyzed using statistical methods and signal processing algorithms to identify activity patterns related to heart conditions. The results of the analysis showed different physical activity patterns between individuals with heart disease and healthy individuals. Individuals with heart disease tend to have lower levels of physical activity and less regular activity patterns. In addition, certain activity patterns, such as long periods of low-intensity activity, are associated with a higher risk for cardiac complications. The implementation of this research is that wearable sensors can be an effective tool in the management of heart disease by enabling accurate monitoring of an individual's physical activity. By analyzing physical activity patterns, we can better understand the relationship between physical activity and heart conditions, allowing for the development of more precise and personalized interventions in the management of heart disease.